Evaluation of leptin serum concentrations during surgery and first-line chemotherapy in primary epithelial ovarian cancer patients - Grabowski, Jacek Przemyslaw; Markowska, Anna; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: The available data on serum leptin levels in ovarian cancer present contradictory results. The majority of authors report lower leptin levels in those patients in comparison to healthy individuals. However, there is no data regarding leptin concentrations during therapy in women with primary epithelial ovarian cancer. Material and methods: Blood samples were collected at the time of diagnosis, after initial surgery, and after first-line chemotherapy. Leptin serum concentrations were analysed using ELISA technique. Additionally, parallel measurements of CA125 levels were performed. Results: Fifty-three patients with primary epithelial ovarian cancer met the inclusion criteria and were included in our study. Our analysis revealed a significant difference in mean preoperative serum leptin concentrations between early and advanced ovarian cancer patients (p < 0.0001). We identified statistically significant elevation of mean serum leptin levels (p < 0.001) after complete macroscopic cytoreduction and after first-line chemotherapy in advanced ovarian cancer cases. Discussion : In this cohort, a significant elevation of postoperative serum leptin levels after complete macroscopic cytoreduction were shown. Moreover, elevation of leptin levels corresponded with remission after chemotherapy. Further studies are needed to determine if leptin can be a potential marker of surgery completeness as well as a marker in chemotherapy response evaluation.